2016
DOI: 10.3389/fpls.2016.01434
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Pattern of Population Genetic Diversity in Three Indo-West Pacific Rhizophora Mangrove Species

Abstract: Rhizophora species are the most widely distributed mangrove trees in the Indo-West Pacific (IWP) region. Comparative studies of these species with shared life history traits can help identify evolutionary factors that have played most important roles in determining genetic diversity within and between populations in ocean-current dispersed mangrove tree species. We sampled 935 individuals from 54 natural populations for genotyping with 13 microsatellite markers to investigate the level of genetic variation, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 101 publications
8
59
1
Order By: Relevance
“…The genetic structure inferred by genome-wide SNPs (Figure 3 tating the accumulation of random genetic divergences (Francisco et al, 2018;Wee et al, 2014;Yan, Duke, & Sun, 2016). Our results also suggest that the lower precipitation of the warmest quarter in northern sites (AMMC and Northeast Brazil regions; Figure 1) may play an additional, nonneutral role in shaping this north-south divergence.…”
Section: Gradual Environmental Variation In Freshwater Availabilitysupporting
confidence: 52%
“…The genetic structure inferred by genome-wide SNPs (Figure 3 tating the accumulation of random genetic divergences (Francisco et al, 2018;Wee et al, 2014;Yan, Duke, & Sun, 2016). Our results also suggest that the lower precipitation of the warmest quarter in northern sites (AMMC and Northeast Brazil regions; Figure 1) may play an additional, nonneutral role in shaping this north-south divergence.…”
Section: Gradual Environmental Variation In Freshwater Availabilitysupporting
confidence: 52%
“…Isolation by distance seem typical of mangroves (Cerón‐Souza et al., ; Kennedy et al., ; Sandoval‐Castro et al., ). However, it has been suggested that factors other than absolute geographic distance should be also considered, including water velocity (Nathan et al., ), the retention of propagules by roots (Van der Stocken et al., ), tides (Ngeve, van der Stocken, Sierens, Koedam, & Triest, ), the direction of wind and local currents, and coastal topography (Yan, Duke, & Sun, ). We hypothesized that the level of genetic structure found on each coast would be related to differences in each coast's features.…”
Section: Discussionmentioning
confidence: 99%
“…GM56), probably following the Gulf current during the Holocene. Previous studies proposed two recolonization routes for the northern parts of the Gulf of Mexico and Florida (Sherrod & McMillan, 1985), from sources in the Yucatan Peninsula and the Caribbean coasts in Central America (McMillan, 1986 along the Gulf of Mexico, which is further backed by the lack of correlation between latitude and heterozygosity along this coast (which remained non-significant even after taking the concave shape of this basin into account; r s = 0.309, P = 0.538; see also (Yan, Duke, & Sun, 2016). We hypothesized that the level of genetic structure found on each coast would be related to differences in each coast's features.…”
Section: Contrasting Post-glacial Population Dynamics Between Gene mentioning
confidence: 99%
“…(Wee et al., ). Although this pattern is not universal—for instance, it was not detected in other Rhizophora (Yan et al., ) and Sonneratia (Yang et al., ) species—it indicates that common extrinsic factors, such as superficial ocean currents (Wee et al., ) and sea‐level fluctuations (Yan et al., ), have shaped the organization and distribution of genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…(Rhizophoraceae; Minobe et al, 2010), Excoecaria agallocha L. (Euphorbiaceae; Zhang et al, 2008), Lumnitzera racemosa Willd. (Combretaceae; Li et al, 2016), Rhizophora apiculata Blume (Rhizophoraceae; Yahya et al, 2014;Yan, Duke, & Sun, 2016), and R. mucronata Lam. (Wee et al, 2014).…”
mentioning
confidence: 99%